The Learning Curve for Peroral Endoscopic Myotomy in Latin America: A Slide to the Right? - Michel Kahaleh; Amy Tyberg; Supriya Suresh; Arnon Lambroza; Fernando Rodriguez Casas; Mario Rey; Jose Nieto; Guadalupe Ma Martínez; Felipe Zamarripa; Vitor Arantes; Maria G Porfilio; Monica Gaidhane; et al. (Clinical Endoscopy, 2021)
Background/Aims Peroral endoscopic myotomy (POEM) has been increasingly used for achalasia in Latin America, where Chagas disease is prevalent, and this makes POEM more challenging. The aim of this study was to determine the learning curve for POEM in Latin America. Method: Patients undergoing POEM in Latin America with a single operator were included from a prospective registry over 4 years. Non-linear regression and cumulative sum control chart (CUSUM) analyses were conducted for the learning curve. Results A total of 125 patients were included (52% male; mean age, 59 years), of which 80 had type II achalasia (64%), and 38 had Chagas disease (30%). The average pre-procedure and post-procedure Eckardt scores were 6.79 and 1.87, respectively. Technical success was achieved in 93.5% of patients, and clinical success was achieved in 88.8%. Adverse events occurred in 27 patients (22%) and included bleeding (4 patients), pneumothorax (4 patients), mucosal perforation (13 patients), mediastinitis (2 patients), and leakage (4 patients). The CUSUM chart showed a median procedure time of 97 min (range, 45-196 min), which was achieved at the 61st procedure. Procedure duration progressively decreased, with the last 10 procedures under 50 min approaching a plateau (p-value <0.01). Conclusions Mastering POEM in Latin America requires approximately 61 procedures for both POEM efficiency and to accomplish the procedure within 97 minutes.